The science of problem solving : a practical guide for science teachers - Watts, Mike. (London : Heinemann Portsmouth, NH, 1991)
Problem solving is a topical teaching method employed in science education. This book looks at individual and group learning in science education. Teaching strategies are fully illustrated with descriptions of projects, role play and coursework. The book stresses the importance of classroom tasks.
Includes bibliographical references and index.
Keywords: Science -- Study and teaching (Secondary).; Problem solving; Science teachers